New designs for siRNAs as Dicer substrate - Behlke, Mark (Henry Stewart Talks, 2007)
Potency of RNA duplexes of ~27 nucleotides in length, Dicer substrates, Variation in dicing patterns, Defined substrate preferences for Dicer, Design of RNA duplexes that are processed to specific, desired products, Dicer processing introduces functional asymmetry into the potency of a RNA duplex, Preferential binding of Dicer to 3'-overhand, The exploitation of Dicer properties to improve design of RNAi reagents
Archived at 2016/10/12